ANALISIS HUBUNGAN SUFISME, PSIKOTERAPI, DAN KESEHATAN SPIRITUAL - Bakar, Usman Abu (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2016)
Analysis on Relations of Sufism, Psychotherapy and Spiritual Health. This paper specifically discusses the relationship of sufism, psychotherapy and spiritual health. Someone with an understanding of Sufi religiosity can be one source of the greatest contributions in its development function of body, mind, and spirit and can be a preventive measure of a person’s health. Psychotherapy is very useful to assist in understanding him/her self, knowing the sources of psychopathology and difficulties of adjustment, as well as providing brighter future perspectives in the life of soul. It also assists in diagnosing patients with forms of psychopathology; and assist patients in determining the practical measures and the implementation of the therapy. For Islam, both worldly and hereafter psychotherapy should be pursued. Hereafter Psychotherapy is guidance and grace (Wahhab) of Allah, which contains ideological and theological framework. While worldly psychotherapy is the result of ijtihad (effort) of human, such as psychiatric treatment techniques that are based on the rules Insaniah. Both models of psychotherapy are equally important, like the currency linked to one another